You are who your friends are?: An experiment on homophily in trustworthiness among friends. (May 2020) - Winter, Fabian; Kataria, Mitesh
We study the existence of homophily (i.e. the tendency for people to be friends with people who are similar to themselves) with respect to trustworthiness. We ask whether two friends show similarly trustworthy behavior toward strangers, and whether such behavior is expected by a third party. We develop a simple model of Bayesian learning in trust games and test the derived hypotheses in a controlled laboratory environment. In the experiment, two trustees sequentially play a trust game with the same trustor, where the trustees depending on treatment are either friends or strangers to each other. We confirm the existence of homophily with respect to trustworthiness. The trustors' beliefs about the trustees' trustfulness are not affected by the knowledge about the (non-)existent friendship between the trustees. Behaviorally, however, they indirectly reciprocate the (un-)trustworthy behavior of one trustee toward his or her friends in later interactions.